VARIABEL-VARIABEL YANG MEMPENGARUHI KEBIJAKAN DIVIDEN - Mohammad Eddy Rosyadi (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
The purpose of this study is to obtain empirical evidence about the factors which influence dividend policy. Independent variables used in this research are managerial ownership, institutional ownership, debt policy,profitability, life cycle stage, and firm size. Population in this research are non financing companies listed in Indonesia Stock Exchange during 2006-2010. Samples are obtained through purposive sampling method. Data are analyzed using multiple regression analysis.The results show that institutional ownership, profitability, and life cycle stage have influence toward dividend policy. Managerial ownership, debt policy, and firm size have no influence toward dividend policy.